Building entrepreneurial character in schools: preparing the young generation for the world of work - Amri, Yul; Monalisa, Afliah (Research in Education and Technology (REGY), 2024)
The entrepreneurial spirit emerges through a long process, especially for those who do not have experience or are not used to being in an environment that supports the growth of the entrepreneurial spirit. Often educational institutions only produce students who are skilled but do not have an entrepreneurial spirit, so that in the end students are formed as workers ready to work, not job creators. Long before, in the process of cultivating an entrepreneurial spirit through education, there was a process of forming an entrepreneurial spirit, namely through a process of learning and habituating oneself as the originator of character in the future. However, if it is related to the needs, hopes, and support of the government for the growth of the entrepreneurial spirit through education, then this matter deserves more attention. The following describes several entrepreneurial activity programs that management can carry out to foster an entrepreneurial spirit for students, namely through entrepreneurship-based extracurricular activities, field trip activities at traditional markets and MSMEs, and holding Bazar at school.